Acquisitions and Technology Value Revision - Cai, Xiangshang; De Cesari, Amedeo; Gao, Ning; Peng, Ni (Management Science, 2024)
Acquisition announcements coincide with upward value revisions for the target firms’ technology peers, which are not due to economic relations based on product market, supply chain, or geographical location. Such a phenomenon is robust across subsample periods, not specific to merger or technology waves, and not related to product-market structure and the unique innovation features of certain technology-intensive industries. Firms experience more dramatic value revisions when they have deeper technology overlaps with their targets, are more dependent on technology, or when a transaction features higher premium or greater technology overlap between the acquirer and target. Our mechanism analysis provides evidence that is primarily consistent with the acquisition-probability hypothesis whereby acquisition announcements elevate expected technology synergies and merger prospects for peers and partially in line with the enhanced-investment hypothesis that peers’ revaluations correlate with increased technology investments. We do not find any evidence in line with the competition-balance hypothesis that attributes peers’ value revisions to the change in industrial competition intensity. Overall, our results demonstrate that acquisition announcements disseminate novel information about the value of technology that is of common interest among firms with close technologies. This paper was accepted by Gustavo Manso, finance. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2023.4890 .